Análise termoestrutural do desencurvamento de placas no lingotamento contínuo - Rafael Fernandes Reis (2019)
The intensity of stresses imposed on the slab, combined with deep oscillation marks and low ductility over a given temperature range, increases the probability of cracking, both on surface and at solidification front. Software ANSYS was used to perform mathematical modeling of slabs straightening. Friction coefficient between slab and rolls, ferrostatic pressure, solidified shell thickness and thermal effects were considered on the structural simulations. A hypo-perictetic niobium microalloyed steel was hot tensioned at temperatures of 800, 900, 1000 and 1100°C and the stress versus strain curves were obtained. The material model proposed by Anand that matches the mechanisms of creep and plasticity using nine constants was evaluated. Two of them were obtained by multiple regression. The Anand’s model was implemented at the ANSYS and compared with the traditional procedure of modeling the two mechanisms separately. The maximum stress observed using Anand’s model was 67.21 MPa while for visco-plastic separately it was 32.20 MPa. The stresses obtained with Anand’s model were higher than the ultimate stress of the steel, indicating the formation of cracks which do not occur in the industrial process. The highest strain for the visco-plastic model was 0.0123 while for the Anand’s model the strains were below 0.0099. Since a strain of 0.033 was estimated by an empirical model it can be concluded that the results of the simulation using the visco-plastic model was more precise than with the Anand’s model. It has been found that the stresses are high with increasing slab width and decreasing casting speed. With casting speed of 0.8m/min, growing slab width of 1200 mm to 1800 mm, stress increase since 30.6 MPa for 37.9 MPa. On casting speed of 1.0 m/min slab growing of 1200 mm to 1800 mm implies in a stress of 28,8 MPa for 32.2 MPa, showing an increase of 12%. Concerning roll misalignment of 1 mm, it was showed that stress growth by 75%, beginning of 32.2 MPa and reaching 56.4 MPa with the same casting speed and slab width. Thus, there is high cracking potential compared with others parameters studied. Similarly, total deformation grows by 70%, being aligned equals to 0,0123 and misaligned 0,021. It was perceived that the increment was correlate mainly to plasticity mechanism.